Influencing factors of different development stages of green food industry: a system dynamic model - Zhai, Xujun; Zheng, Lian; Ma, Guifang; Lin, Hong (Frontiers in Environmental Science, 2024)
The green food industry is important for China because it bears the additional expectation of prospering the rural economy. Heilongjiang Province is a representative example, which is one of the main production bases of green food. With this in mind, this paper takes Heilongjiang Province as an example to research the main influencing factor of the green food industry. Different from previous studies, this paper divides the life cycle of the industry and discusses the effects of influencing factors during the different periods. The main conclusion includes: The stage before 2011 is the germination period, the stage from 2011 to 2019 is the growth period, and the stage after 2019 is the maturity period. By the final time of the simulation, there are no signs of faltering; The enterprise scale is the main influencing factor that can make positive effects on the output value of the green food industry from the growth period, and others have no obvious impact from beginning to end; Undesirably high level of financial investment will exert a negative effect for industrial development in the maturity period, at least in terms of output value.